Postdramatic tragedy and fear : the case of Socìetas Raffaello Sanzio's Tragedia Endogonidia - Bauer, Una (Array, 2020)
This article engages with conceptual constellations which allow a contemporary postdramatic theatre production, specifically Socìetas Raffaello Sanzio’s theatrical series Tragedia Endogonidia (2002 – 2004) to be regarded as a tragedy or a series of tragedies. Particular emphasis is given to the role of fear in understanding Tragedia Endogonidia as a tragedy. My claim is that Tragedia Endogonidia contributed to the modification of contemporary understanding of tragedy to, at the same time, a more abstract and a more explicitly material one, where the anchoring of the tragic into a concrete human destiny and the resolution of a plot is replaced by “plotting of the sensorial” or “plotting of the image”, driven by anticipation directly related to an unspecified feeling of discomfort and fear.